On the process capability of the solid free-form fabrication: a case study of scaffold moulds for tissue engineering. - Liu, C; Han, Z; Hourd, P; Czernuszka, J (2008)
This study applies the methodology and procedure of process capability to investigate a solid free-form fabrication technique as a manufacturing method to produce scaffold moulds for tissue engineering. The process capability Cpk and process performance Ppk of scaffold mould manufacture using a solid free-form fabrication technique has been analysed with respect to the dimension deviations. A solid free-form fabrication machine T66 was used to fabricate scaffold moulds in this study and is able to create features that ranged from 200 microm to 1000 microm. The analysis showed that the printing process under the normal cooling conditions of the printing chamber was in statistical control but gave low process capability indices, indicating that the process was 'inadequate' for production of 'dimension-consistent' scaffold moulds. The study demonstrates that, by lowering the temperature of the cooling conditions, the capability Cpk of the printing process can be improved (about threefold) sufficiently to ensure the consistent production of scaffold moulds with dimension characteristics within their specification limits.